Using artificial intelligence methods for the optimal synthesis of reversible networks - Taras Kyryliuk; Mykhailo Palahuta; Vitaly Deibuk (Радіоелектронні і комп'ютерні системи)
Considering the relentless progress in the miniaturization of electronic devices and the need to reduce energy consumption, technical challenges in the synthesis of circuit design solutions have become evident. According to Moore's Law, the reduction of transistor sizes to the atomic scale faces physical limits, which complicate further development. Additionally, reducing transistor sizes causes current leakage, leading to increased thermal noise, which can disrupt the proper functioning of digital devices. A promising solution to these problems is the application of reversible logic in circuit design. Reversible logic allows for a reduction in energy and information losses because logical reversible operations are performed without loss. The research synthesized optimal reversible circuits based on reversible gates using evolutionary algorithms and compare them with existing analogues. The focus of this study is on logical circuits built using reversible gates, which can significantly reduce energy losses, which is critical for modern and future electronic devices. The synthesis of reversible circuits is closely related to quantum computing, where quantum gates also possess a reversible nature. This enables the use of synthesis methods to create quantum reversible logical computing devices, which in turn promotes the development of quantum technologies. The study focuses on the application of evolutionary artificial intelligence algorithms, specifically genetic algorithms and ant colony optimization algorithms, for the optimal synthesis of reversible circuits. As a result, a detailed description of the key concepts of the improved algorithms, simulation results, and comparison of the two methods is provided. The efficiency of the reversible device synthesis was evaluated using the proposed implementation of the genetic algorithm and the ant colony optimization algorithm. The obtained results were compared to existing analogs and verified using the Qiskit framework in the IBM quantum computing laboratory. The conclusions describe the developed algorithms, which demonstrate high efficiency in solving circuit topology optimization problems. A genetic algorithm was developed, featuring multi-component mutation and a matrix approach to chromosome encoding combined with Tabu search to avoid local optima. The ant colony optimization algorithms were improved, including several changes to the proposed data representation model, structure, and operational principles of the synthesis algorithm, enabling effective synthesis of devices on the NCT basis along with Fredkin gates. An improved structure for storing and using pheromones was developed to enable multi-criteria navigation in the solution space.